Cognition and work : a study concerning the value and limits of the pragmatic motifs in the cognition of the world - Scheler, Max, 1874-1928 (Northwestern University studies in phenomenology & existential philosophy., 2021)
"In Cognition and Work, Max Scheler offers an early critique of American pragmatism and demonstrates the dynamic relation that not only the human being but all living beings have to the environment they inhabit"--